Cilium assembly and disassembly - Sánchez, Irma (Nat Cell Biol, 2016)
The primary cilium is an antenna-like, immotile organelle present on most types of mammalian cells, which interprets extracellular signals that regulate growth and development. Although once considered a vestigial organelle, the primary cilium is now the focus of considerable interest. We now know that ciliary defects lead to a panoply of human diseases, termed ciliopathies, and the loss of this organelle may be an early signature event during oncogenic transformation. Ciliopathies include numerous seemingly unrelated developmental syndromes, with involvement of the retina, kidney, liver, pancreas, skeletal system and brain. Recent studies have begun to clarify the key mechanisms that link cilium assembly and disassembly to the cell cycle, and suggest new possibilities for therapeutic intervention.